2009
DOI: 10.1002/pssa.200881468
|View full text |Cite
|
Sign up to set email alerts
|

Helium implantation into 4H‐SiC

Abstract: The paper provides the properties of single crystalline 4H-SiC under helium implantation at temperatures of implantation up to 750 ◦C and fluences in the range 5×1015-1×1017 cm−2. The microstructure evolution was studied by transmission electron microscopy cross- section and X-ray diffraction experiments. The mechanical property changes were investigated by using nanoindentation tests followed by atomic force microscopy observations and by using tribological tests. At elevated temperature of implantation and/o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 30 publications
2
13
1
Order By: Relevance
“…For the specimens implanted to 30 (0.44 dpa) and 150 (2.2 dpa) at. ppm Xe, the absence of a plateau or peak at low angle beside the main peak indicates that the implant region has been amorphized [7]. It is in agreement with previous results [15,16] which demonstrate amorphization of SiC is achieved at $0.25-0.4 dpa.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…For the specimens implanted to 30 (0.44 dpa) and 150 (2.2 dpa) at. ppm Xe, the absence of a plateau or peak at low angle beside the main peak indicates that the implant region has been amorphized [7]. It is in agreement with previous results [15,16] which demonstrate amorphization of SiC is achieved at $0.25-0.4 dpa.…”
Section: Resultssupporting
confidence: 89%
“…Previous studies have shown that the strain induced by He ion implantation in SiC is strongly localized along the direction perpendicular to the implanted surface [5], causing the lattice to expand. For elevated temperature He ion implants, amorphization of the crystal can be avoided due to dynamical annealing, and the strain profiles show thermally activated saturation in the near-surface region indicating that a threshold concentration of defects is reached [6,7], whereas the strain profiles also show that defect accumulation occurs near the damage peak [7]. Recently it has been demonstrated that in extended surface region both the accumulation of interstitial atoms drifted to the deeper damaged region and the recombination of point defects are enhanced by strain gradient and temperature, resulting in the nearly constant strain that levels off at sufficient fluence [8].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on inert gas atoms in silicon carbide were mainly focused on microstructural evolution after helium implantation [4][5][6][7][8][9][10], but fewer efforts were paid on effects of implantation with heavier inert gas ions. Compared with helium implantation, more displacements of lattice atoms can be produced in one collision cascade by an incident heavier inert-gas ion.…”
Section: Introductionmentioning
confidence: 99%
“…Ion implantation technique is an alternative method to study irradiation damage in materials within a relatively short period of time. Helium ions were implanted into 4H-SiC in the work of Barbot et al [10], and amorphous layers were observed beneath the surface exposed to helium ions. Such irradiation-induced amorphization was reported to cause an increase in fracture toughness due to the formation of microcracks which dissipate the strain energy.…”
Section: Introductionmentioning
confidence: 99%